Medical treatment and long-term outcome of chronic atrial fibrillation in the aged with chest distress: a retrospective analysis versus sinus rhythm - Guo Y (Dove Medical Press, 2011)
Yutao Guo, Lu Zhang, Chunjiang Wang, Yuexiang Zhao, Weiren Chen, Meng Gao, Ping Zhu, Tingshu Yang, Yutang WangDepartment of Geriatric Cardiology, General Hospital of The Chinese PLA, Beijing, 100853, People’s Republic of ChinaAbstract: Although “chest distress” is the most frequent complication in the aged with chronic atrial frbrillation (AF) in clinical practice, there are few data on the association between chronic AF and coronary artery disease (CAD) in the aged in terms of medical treatment and long-term outcome. We assessed coronary artery lesions in such patients and evaluated the efficacy of medical treatment in long-term follow-ups. Of 315 elderly patients (mean age: 77.39 ± 6.33 years) who had undergone coronary angiography for chest distress, 297 exhibited sinus rhythm (SR), whereas 18 patients exhibited chronic AF. Patients with AF were followed for 4.22 ± 2.21 years. Average diastolic blood pressure (DBP) of AF patients was observed to be markedly less than that of patients with SR (57.33 ± 6.87 mmHg vs 71.08 ± 10.54 mmHg, t-test: P < 0.01). Compared with SR patients, severe stenosis of the coronary artery in AF patients was reduced (73.06% vs 44.44%, Chi-square test: P < 0.01). AF patients with chest distress had high CHADS2 score (3.72 ± 1.27), but only 33.3% patients received oral anticoagulants, and such patients had a significantly lower rate of revascularization (21.43% vs 55.63%, Chi-square test: P < 0.01), and higher rate of all-cause death (22.22% vs 4.38%, Chi-square test: P < 0.01) and thromboembolism (16.67% vs 1.68%, Chi-square test: P < 0.01) in the long-term follow-ups compared with SR patients. Chest distress in the aged with AF was related to insufficient coronary blood supply that was primarily due to a reduced DBP rather than to occult CAD. Adequate and safe medical therapy was difficult to achieve in these patients. Such patients typically have a poor prognosis, and optimal therapeutic strategies to treat them are urgently needed.Keywords: aging, atrial fibrillation, coronary artery disease, antithrombotic therapy, revascularization, outcome